ANALISIS KEBERLANJUTAN KAWASAN WISATA MANDEH PROVINSI SUMATERA BARAT - Aulia Rahman Pratama; Iswandi U (JURUSAN GEOGRAFI FIS UNP, 2020)
This study aimed to (1) to determine the index and sustainability status of the Mandeh Tourism Area, (2) to find out the sustainability index and status of each dimension (ecological, economic, and social) of the Mandeh Tourism Area. This type of research was quantitative descriptive research. This study used research subjects that had links about tourism, the environment, disaster and the area of ​​the Mandeh Tourism Area. Data analysis techniques used were using the Multi Diemnsional Scaling (MDS) approach that was developed into the Rapfish (Rapid Appraisal of Fisheries) application, Leverage analysis and Monte Carlo analysis. The dimensions used for the assessment of the sustainability analysis of the Mandeh Tourism Area used the ecological, economic and social dimensions which included 24 attributes in each dimension. This study found that: (1) the index and the sustainability status of the Mandeh Tourism Area at (IKb-KWM) was 78.82 with very sustainable status, (2) the index and sustainability status of each dimension was, the ecological dimension was 76.42 with very sustainable, an economic dimension was 85.69 with a very sustainable status, and a social dimension of 85.34 with a very sustainable status.